2013
DOI: 10.1111/josh.12060
|View full text |Cite
|
Sign up to set email alerts
|

Changing Multiple Adolescent Health Behaviors Through School‐Based Interventions: A Review of the Literature

Abstract: A multi-behavior, multi-actor approach would appear to be the most effective way to promote, at school, healthy behaviors among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 56 publications
(228 reference statements)
2
51
0
7
Order By: Relevance
“…This study, like the previous ones conducted by the same team [5, 21, 29], confirms that school is an important setting for the promotion of mental health [30] and that these initiatives can be successful if (a) they are structured and evidence-based [31]; (b) they are directed towards changing behavioural aspects related to specific objectives that take into account the everyday life of the student in relation to the family environment and the surrounding community [10]; (c) they encourage greater sharing among students of both aspects of the curricular goals and personal/interpersonal growth [32, 33]. …”
Section: Discussionsupporting
confidence: 86%
“…This study, like the previous ones conducted by the same team [5, 21, 29], confirms that school is an important setting for the promotion of mental health [30] and that these initiatives can be successful if (a) they are structured and evidence-based [31]; (b) they are directed towards changing behavioural aspects related to specific objectives that take into account the everyday life of the student in relation to the family environment and the surrounding community [10]; (c) they encourage greater sharing among students of both aspects of the curricular goals and personal/interpersonal growth [32, 33]. …”
Section: Discussionsupporting
confidence: 86%
“…They also noted the existence of a discernible gap in the use of qualitative research designs to examine HPS. Consistent with the work of Busch et al (2013), findings by Bonell et al (2013) and Samdal and Rowling (2011) (Deschesnes, Trudeau, & Kébé, 2010;McIsaac, Read, Veugelers, & Kirk, 2013;McIsaac, Sim, Penney, Kirk, & Veugelers, 2012) underscored the importance of culture and collaboration among HPS stakeholders. However, there is little discussion in the literature regarding how the HPS school environment affects students and their families.…”
Section: Hps Researchsupporting
confidence: 67%
“…Despite extensive recognition of the central role of teachers and the curriculum in HPS programming, educational research on the contribution of schooling to health decision-making is reported to be scant (Lee 2009;Venka, 2012). Busch, de Leeuw, de Harder, and Schrijvers (2013) observed uncertainty regarding the effectiveness of the HPS model, particularly in relation to role of parents and the impact of school environments on students' health and wellbeing. They also noted the existence of a discernible gap in the use of qualitative research designs to examine HPS.…”
Section: Hps Researchmentioning
confidence: 99%
“…Such knowledge is essential for educational stakeholders who advocate for adequate and equitable access to facilities and activities that promote physical activity. Indeed, school administrators are constantly in need of up‐to‐date knowledge to support their efforts to build healthy environments in their schools in general, and in particular, to implement interventions that integrate with the existing school infrastructure . For example, improving access to existing outdoor facilities or signing municipal agreements to use nearby available spaces to offer diverse PAS opportunities in school zones, are inexpensive options illustrated by our study.…”
Section: Implications For School Healthmentioning
confidence: 96%